(untitled) (Universal International Scientific Journal, 2026)
This article examines the goals and objectives of providing inclusive education to children with disabilities. It also discusses the integration of children with special educational needs into society, as well as the problems in this field and possible solutions. In addition, the importance of promoting inclusive education among teachers in primary education is highlighted.